2015
DOI: 10.1364/oe.23.022857
|View full text |Cite
|
Sign up to set email alerts
|

High-power dual-fed traveling wave photodetector circuits in silicon photonics

Abstract: We introduce the concept of dual-illuminated photodetectors for high-power applications. Illuminating the photodetector on both sides doubles the number of optical channels, boosting DC and RF power handling capability. This concept is demonstrated utilizing multiple-stage dual-illuminated traveling wave photodetector circuits in silicon photonics, showing a maximum DC photocurrent of 112 mA and a 3-dB bandwidth of 40 GHz at 0.3 mA. Peak continuous-wave RF power is generated up to 12.3 dBm at 2 GHz and 5.3 dBm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…1a). This reduction in germanium area allows higher optical powers to be absorbed, and feeding from both ends of the photodetector increases efficiency [6]. For an individual TWPD, the photodetectors are placed in parallel as part of the transmission line between the GSG pads [7], in which one side is a termination (L) and the other side is the receiver (S) (see Fig.…”
Section: Traveling-wave Photodetectormentioning
confidence: 99%
“…1a). This reduction in germanium area allows higher optical powers to be absorbed, and feeding from both ends of the photodetector increases efficiency [6]. For an individual TWPD, the photodetectors are placed in parallel as part of the transmission line between the GSG pads [7], in which one side is a termination (L) and the other side is the receiver (S) (see Fig.…”
Section: Traveling-wave Photodetectormentioning
confidence: 99%
“…By adding a splitter in front of the PD, the linearity can be improved at the cost of a slight increase in insertion loss (due to the excess loss of the splitter, which is specified to be below 0.2 dB). This enhanced power handling capability is caused by the increased portion of the absorption layer that is used for the opto-electronic conversion [14].…”
Section: Dual Fed Photodetectorsmentioning
confidence: 99%
“…To make optimal use of the aforementioned benefits of silicon photonics, a high-power variant of the existing Si-integrated Ge PiN photodetector needs to be constructed without altering the technology stack of the iSiPP25G platform or requiring heterogeneous integration. The traveling wave photodiode (TWPD) structure is the most popular configuration to realize high power handling while relying on high-speed p-i-n photodetectors [14]. In this paper, a highpower-handling traveling wave photodetector (TWPD) structure integrated on a silicon photonics waveguide platform will be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, a foundry service provides crosssection information and models of building blocks to clients, who design a photonic integrated circuit (PIC) [1] to fit their own specific needs. Recent demonstrations of high-speed PICs fabricated using foundry services [2][3][4] have shown that it is possible to design PICs with performance better than that of single building blocks. In order for first-time-correct designs to become consistently achievable, accurate microwave impedance models must be included in foundry libraries.…”
Section: Introductionmentioning
confidence: 99%